Oral traditions of the Kerinci community: proverbs, sayings, and old rules - Helida, Asvic; Zuhud, Ervizal Amir Muhammad (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
Proverb of a community can indicate their level of knowledge on natural resource and forest management. These expressions are an effective way to learn about traditional ecological knowledge (TEK). Differences or similarities in the knowledge systems of various ethnic groups can be found by comparing their expressions. This traditional ecological knowledge is passed down from generation to generation through oral tradition. Oral traditions are not always reliable because they depend on memory and oral transmission. However, unlike proverbs, old sayings and societal rules have more validity by their nature. Proverbs and old sayings are expressions of fundamental truths or practical perceptions based on common sense or cultural experience. The Kerinci community in Kerinci Regency, Jambi Province, is known to have these expressions, but it has not been documented. Therefore the significance of this research needs to be done. The maintenance of expressions of oral tradition is a task from generation to generation simultaneously so that the collection of expressions in the form of proverbs, proverbs, and local rules from a community group becomes essential for the development of science. This study aims to document and analyze the expressions of the people of Kerinci. The research method was carried out qualitatively with library research techniques and interviews with resource persons. The results show that there are 30 expressions of the Kerinci community consisting of proverbs and old rules. These expressions show that the people of Kerinci have the knowledge they get from nature and the ecosystem in which they live.